Mitochondrial Myopathy with DNA Depletion - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Five children with mitochondrial myopathy associated with depletion of muscle mtDNA are reported from the Departments of Neurology and Genetics and Development, Columbia University College of Physicians and Surgeons, New York, NY and other centers in Germany, Belgium and the U.S.